2013
DOI: 10.1002/14651858.cd006203.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for treating traumatised permanent front teeth: luxated (dislodged) teeth

Abstract: Interventions for treating traumatised permanent front teeth: luxated (dislodged) teeth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
10

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 33 publications
2
13
0
10
Order By: Relevance
“…10 Randomization is difficult to perform in dental trauma studies due to its low incidence, emergency nature, and the fact that it requires a multi-professional treatment approach in many cases. 21,28 The absence of randomization in these studies elicits other problems. The protocols differed not only from one study to another, but also, and without explanation, within the same study, where a treatment group that should have been homogeneous was not.…”
Section: Discussionmentioning
confidence: 99%
“…10 Randomization is difficult to perform in dental trauma studies due to its low incidence, emergency nature, and the fact that it requires a multi-professional treatment approach in many cases. 21,28 The absence of randomization in these studies elicits other problems. The protocols differed not only from one study to another, but also, and without explanation, within the same study, where a treatment group that should have been homogeneous was not.…”
Section: Discussionmentioning
confidence: 99%
“…This highlights the need for consensus on the minimum period of follow up for TDI. The two Cochrane reviews in dental traumatology have identified that for periodontal healing, this period should be a minimum of 12 months (1,14). This time period, however, is too short to collect robust data for outcomes such as tooth loss (24).…”
Section: Discussionmentioning
confidence: 99%
“…Arrangements were made to translate and assess studies that were not published in English (13). One of the authors (PD) has been involved with a number of Cochrane reviews, and research papers translated for these reviews were also used where appropriate in this publication (1,14).…”
Section: Languagementioning
confidence: 99%
“…Dabei sollte die Reposition langsam erfolgen, um keine iatrogene Wurzelfraktur zu verursachen [6]. Die optimale Versorgung intrudierter Zähne hingegen ist umstritten.…”
Section: Luxationsverletzungen Und Avulsionunclassified